Analisis Pengaruh Kebijakan Tax Holiday Terhadap Perkembangan Penanaman Modal Asing di Indonesia (Tahun 1970-1999) - Kesit Bambang Prakosa (Economic Journal of Emerging Markets, 2003)
Investment is an important key for economic growth of a nation, in fact even for developing countries such as Indonesia. There are several factors affecting foreign direct investment coming to a nation. The goal of this research is to analyze the implementation of tax incentive to the behavior of foreign direct investment. Beside this, in general the aim of research is to identify the impact of product domestic bruto, national saving and tax upon the level of foreign direct investment coming to Indonesia during period 1970-1999.By Using regression analysis, the result show that foreign direct investment in Indonesia is affected positively by product domestic bruto and tax incentive that is PP No. 45/1996. The tax incentive given by the government, however, attracts less foreign direct investment. In other hand, by using qualitative analysis, the decision of foreign investors depend upon empirically not only the economic factors but also the non-economics factors.Based on the situation above, the study suggests that in order to achieve an optimum investment policy, the economic policy need to support the consistency and transparency of the government policy, create the political and social stability and secure in doing business activities in domestic market. In addition, good infrastructure is incentive too for the foreign direct investment because it leads to decrease the investment cost.  Keyword: foreign direct investment, product domestic bruto, tax incentive